Synergistic Insecticidal Activity of Plant Volatile Compounds: Impact on Neurotransmission and Detoxification Enzymes in Sitophilus zeamais - Leidy J. Nagles Galeano; Juliet A. Prieto-Rodríguez; Oscar J. Patiño-Ladino (Insects)
Sitophilus zeamais, a major pest of stored grains, causes significant post-harvest losses and challenges effective control. While synthetic insecticides pose risks of resistance and toxicity, essential oils (EOs) offer a safer alternative. However, the insecticidal potential of their individual volatile constituents (VCs) remains largely unexplored. This study evaluated the insecticidal activity of 51 EO-derived volatile compounds (VCs) against S. zeamais, identifying the most toxic ones, optimizing 15 synergistic mixtures, and assessing their effects on key insect enzymes. A structure–activity relationship (SAR) analysis determined functional groups associated with insecticidal activity, while a cluster analysis pre-selected 29 ternary mixtures, later refined using response surface methodology (RSM). Additionally, enzymatic assays explored their impact on detoxification and nervous system enzymes, providing insights into potential mechanisms of action. Among the 51 VCs tested, 37 exhibited significant toxicity, with 11 acting as fumigants and 13 displaying contact toxicity. Monocyclic monoterpenoids with ketone or alcohol functional groups and exocyclic unsaturation demonstrated the highest insecticidal activity via both exposure routes. Notably, pulegone enantiomers were particularly effective (LC50 < 0.1 mg/L, LD50 < 7.5 µg/adult). Among the optimized mixtures, 10 displayed strong insecticidal effects, 8 were active through both routes, and 5 exhibited synergistic fumigant interactions. The most effective formulations were M2 (R-pulegone + S-pulegone + S-carvone, LC50 0.48 mg/L) and M20 (isopulegone + δ-3-carene, LC50 2.06 mg/L), showing the strongest fumigant and synergistic effects, respectively. Enzymatic assays revealed that while some compounds mildly inhibited GST and CAT, others, such as δ-3-carene (IC50 0.19 mg/L), significantly inhibited AChE. Five mixtures exhibited synergistic neurotoxicity, with M20 (IC50 0.61 mg/L) and M12 (IC50 0.81 mg/L) emerging as the most potent AChE inhibitors. These findings highlight the potential of plant-derived volatile compounds as bioinsecticides, leveraging synergistic interactions to enhance efficacy, disrupt enzymatic pathways, and mitigate resistance.